ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI LINGKARAN - Maul Jannah; Indra Budiman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to describe students mathematical critical thinking skills in solving circle problems.. This type of research is descriptive qualitative, using the subject of 12 students of class XI at MA Nurussa'adah Pakuhaji. The research data collection technique is observation. The instrument is in the form of two description test questions. Data analysis in this study uses data reduction, data presentation, and drawing conclusions. The results of the study indicate that students with high levels of critical thinking skills can perform well in all indicators of mathematical critical thinking skills, namely on indicators of interpretation, analysis, evaluation, and inference. Students with moderate critical thinking levels can achieve mathematical critical thinking indicators, namely interpretation, analysis and inference, but are still not perfect in the evaluation indicators. Students with low critical thinking levels still have not completed and fulfilled all the indicators of mathematical critical thinking.